Synthesis of three deoxy-sophorose derivatives for evaluating the requirement of hydroxy groups at position 3 and/or 3' of sophorose by 1, 2-β-oligoglucan phosphorylases. (October 2018) - Tanaka, Nobukiyo; Nakajima, Masahiro; Aramasa, Hiroki; Nakai, Hiroyuki; Taguchi, Hayao; Tsuzuki, Wakako; Komba, Shiro
Abstract: Sophorose (Sop2 ) is known as a powerful inducer of cellulases in Trichoderma reesei, and in recent years 1, 2-β-D-oligoglucan phosphorylase (SOGP) has been found to use Sop2 in synthetic reactions. From the structure of the complex of SOGP with Sop2, it was predicted that both the 3-hydroxy group at the reducing end glucose moiety of Sop2 and the 3′-hydroxy group at the non-reducing end glucose moiety of Sop2 were important for substrate recognition. In this study, three kinds of 3- and/or 3′-deoxy-Sop2 derivatives were synthesized to evaluate this mechanism. The deoxygenation of the 3-hydroxy group of D-glucopyranose derivative was performed by radical reduction using a toluoyl group as a leaving group. The utilization of a toluoyl group that plays two roles (a leaving group for the deoxygenation and a protecting group for a hydroxy group) resulted in efficient syntheses of the three target compounds. The NMR spectra of the two final compounds (3-deoxy- and 3, 3′-dideoxy-Sop2 ) suggested that the glucose moiety of the reducing end of Sop2 can easily take on a furanose structure (five-membered ring structure) by deoxygenation of the 3-hydroxy group of Sop2 . In addition, the ratio of the five- and six-membered ring structures changed depending on the temperature. The SOGPs exhibited remarkably lower specific activity for 3′-deoxy- and 3, 3′-dideoxy-Sop2, indicating that the 3′-hydroxy group of Sop2 is important for substrate recognition by SOGPs. Graphical abstract: Highlights: The 3- and/or 3′-deoxy-sophorose derivatives were synthesized using a toluoyl group. Some 3-deoxy-sophorose derivatives readily take the furanose structure. Both 3- and 3′-OH in sophorose are important for 1, 2-β-oligoglucan phosphorylase.